Communal justice in Calahuyo: Its conflict resolution bodies - Peña Jumpa, Antonio (1991)
Justice in the peasant community of Calahuyo can be studied on two planes or levels: within the plane of valorization or abstraction of fairness, an activity carried out by the community members daily in their economic, social and cultural practices, and that we understand as the basis of communal justice; and, second, within the plane of the materialization or vindication of what is fair, that the community members implement from a rationality and their own procedures and bodies in the face of their conflicts, which constitutes their judicial system.